2020
DOI: 10.3390/ijerph17103525
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary or Forced: Different Effects of Personal and Social Norms on Urban Residents’ Environmental Protection Behavior

Abstract: It is well known that environmental protection behaviors are influenced by both individual internal motivation and external environmental pressure, but few studies have looked at the two kinds of factors together. In order to study the influence mechanism of these two kinds of factors on the environmental protection behavior of urban residents, especially the difference between these two kinds of factors, we take personal norms and social norms as independent variables into the theoretical model. Results based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…The finding is further consistent with investigations of voluntary versus forced behaviour in environmental protection behaviour (e.g. Bai & Bai, 2020), identifying that voluntary behaviour based on personal norms and choice has a greater impact on environmental protection behaviour than mandated behaviour. Consequently, the presentation of behaviours as norms combined with nudging techniques may prove useful as an additional technique next to rule-based strategies in increasing adherence.…”
Section: Factors Associated With Adherence To Sdpssupporting
confidence: 88%
“…The finding is further consistent with investigations of voluntary versus forced behaviour in environmental protection behaviour (e.g. Bai & Bai, 2020), identifying that voluntary behaviour based on personal norms and choice has a greater impact on environmental protection behaviour than mandated behaviour. Consequently, the presentation of behaviours as norms combined with nudging techniques may prove useful as an additional technique next to rule-based strategies in increasing adherence.…”
Section: Factors Associated With Adherence To Sdpssupporting
confidence: 88%
“…This finding is consistent with the theory of intrinsic motivation and self-determination (Deci & Ryan, 1985), highlighting that with regards to sustained behavior change, external strategies and motivators have reduced efficiency in the long-term. The finding is further consistent with investigations of voluntary versus forced behavior in environmental protection behavior (e.g., Bai & Bai, 2020), identifying that voluntary behavior based on personal norms and choice have a greater impact on environmental protection behavior than mandated behavior. Consequently, the presentation of behaviors as norms combined with nudging techniques may prove useful as an additional technique next to rule-based strategies in increasing adherence.…”
Section: Factors Associated With Adherence To Social Distancing Protosupporting
confidence: 87%
“…Measurement items that have been confirmed reliable and valid in previous studies [5,21,36,42,[48][49][50][51] were adapted for this study, and 23 of them were used. Specifically, four question items, including 'This hotel completely uses low flow toilets and good sanitation practices,' were used to measure its water conservation management.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Therefore, customers' revisit is a very important factor for generating profits and future growth of the company, and it is perceived as an important success factor of every company [39]. Consequently, the importance and necessity of revisit have been emphasized in many studies because customer revisit plays an absolutely important role in corporate performance [40][41][42]. In particular, many studies have demonstrated a causal relationship between a company's eco-friendly activities and customers' intention to revisit.…”
Section: Willingness To Pay More and Revisit Intentionmentioning
confidence: 99%